Frequency and types of hemoglobinopathies in children with microcytic anemia - Khan, Sabeen; Sahira Aaraj; Syeda Namayah Fatima Hussain (Journal of the Pakistan Medical Association, 2020)
Abstract Objective: To study the frequency and types of haemoglobinopathies in children with microcytic anaemia. Method: The prospective study was conducted at the Paediatric Out-patient Department of Shifa Falahi Community Health Centre, Islamabad, Pakistan, from July to December, 2018, and comprised patients aged from 3 months to 14 years who had haemoglobin <10mg/dl and mean corpuscular volume <70fL. Serum ferritin and haemoglobin electrophoresis were done to check for iron deficiency anemia and haemoglobinopathies. Data was analysed using SPSS 23. Results: Of 175 subjects, 33(18.9%) had haemoglobinopathies and 142(81.1%) had iron deficiency anaemia. Thalassemia trait 18(10.3%) was the leading cause amongst haemoglobinopathies, followed by thalassemia major 8(4.6 %) and intermedia 5(2.9%). There were 2(1.1%) patients with haemoglobin D. Conclusion: The prevalence of hemoglobinopathies was high. Identification of haemoglobinopathies is important for proper treatment, antenatal screening and future genetic counselling. Key Words: Haemoglobinopathy, Iron deficiency anaemia, Microcytic, MCV, IDA.